2014
DOI: 10.1007/s11136-014-0663-2
|View full text |Cite
|
Sign up to set email alerts
|

Factorial structural analysis of the Spanish version of WHOQOL-BREF: an exploratory structural equation model study

Abstract: As has been suggested by some studies on the application of ESEM, it is reasonable to think that the ESEM approximation is a useful approach for conducting the factor analysis of instruments measuring complex psychological phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
2
25
0
2
Order By: Relevance
“…The results showed that the WHOQOL-BREF is a valid tool. However, some studies have failed to validate it [14,15]. Those studies recruited healthy young samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the WHOQOL-BREF is a valid tool. However, some studies have failed to validate it [14,15]. Those studies recruited healthy young samples.…”
Section: Discussionmentioning
confidence: 99%
“…The WHOQOL-BREF has been used in Singapore to predict adherence to treatment, and to measure the impact of pathologies on QOL and intervention outcomes [7][8][9][10][11]. However, its psychometric properties have not been clearly established in Singapore yet, and although the WHOQOL-BREF has been established to have cross-culturally validity [12,13], not all studies have successfully validated the tool [14,15]. It is critical to validate the tool in Singapore, as the employment of valid measures is necessary to attain valid research conclusions that will inform social service and rehabilitation programs.…”
mentioning
confidence: 99%
“…Con relación a la estructura factorial se obtuvieron medidas aceptables en el modelo final, sin embargo difiere ligeramente del original, resultados que coinciden con otros trabajos que lo han evaluado (Benitez-Borrego et al, 2014).…”
Section: Discussionunclassified
“…This questionnaire has been validated cross-culturally with a high validity, internal consistency and test-retest reliability [25]. The WHOQOL-BREF has been translated into Spanish and has been used in many Spanish speaking countries, including Colombia [39, 40]. In Colombia, this questionnaire has been used among individuals attending the private practice of a bariatric surgeon from Medellín, people affected by HIV/AIDS in Medellín and women with breast cancer in Antioquia [4143].…”
Section: Methodsmentioning
confidence: 99%